CONTROVERSIES ON THE NATIONAL EDUCATION EXAMINATION POLICY - Raihan Iskandar; Mukhneri Mukhtar; Neti Karnati (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This study aims at describing and finding out the root cause of controversies on the national education examination policiy especially on the formulation of laws on the administration of the national examination. The controversies started when the national examination was deemed to determine whether a student graduated from his school or not, while the regulations at the higher level did not really stipulate it. In fact, they almost tended to deny it. These controversies then resulted in deviations and systemic moral hazards in many regions since schools tended to achieve high levels of graduation. These controversies reached their peak when some individuals’ lawsuit was accepted by the Supreme Court and the government’s plea was rejected. Moreover, the government was deemed to neglect its citizens’ human rights. Eventually, these controversies on the national examination challenged the government to reorganize its policy and enhance its valuation standard on the national education system. This study employed qualitative research approach the method of which was intrinsic case study intensively focusing on controversies on the national examination policy as the determinant on a student’s graduation. The data were obtained from national education’s policy makers both from executive branch and from the legislature branch, and from school principals and regional heads of educational department as the field executors who became crucial elements in implementing those policies. The result show that Lack of adequate long-term strategic plans in realizing the educational standard and its evaluation was one of the causes on these controversies. Policy making process errors in fact bred various conflicts in their implementations. The society’s active participation significantly affect the government’s policy change process. Keywords: The National Examination, Controversies, Policy Formulations